Formation of modern light urbanism na primer g. Astana - Sadykova Сара; Abish Гульдана (Рroblems of engineering and professional education, 2023)
The topical issues of forming light urban environment by the example of the city of Astana is considered. The peculiarities of light architecture of the capital city, typology of lighting urban spaces and areas of light compositional fundamental problems, the latest of lighting technology is revealed. The main aspects of the formation of a light architecture considered in stages on more significant examples of Astana.